Evaluation of the Single-Dose Toxicity of Capsaicin Pharmacopuncture in Rats - Ji Hye Hwang; Jaseung Ku; Chul Jung (Journal of Acupuncture Research, 2020)
Background This study aimed to assess the toxicity of capsaicin (CP) pharmacopunture in an animal model. Methods The toxicity of a single-muscular dose of CP (45.45 mg/mL) was evaluated in 6-week-old male and female Sprague-Dawley rats. A total of 20 rats were assigned to 2 groups which were sex and weight matched. All rats acclimatized for 1 week before receiving 1.0 mL of CP (45.45 mg/mL) or normal saline solution (control) intramuscularly. The general condition and mortality of the animals were observed. The rats were sacrificed 2 weeks after CP was administered and histopathology was performed. Results No abnormal symptoms or deaths were observed, and there was no difference in body weights between the CP and control groups throughout the study. No significant differences in histopathology were observed between the groups. Conclusion No toxicological changes related to the administration of CP were observed. This study indicated that the safe dose of CP in Sprague-Dawley rats was 1.0 mL of CP (45.45 mg/mL) or less. Further studies are needed to confirm the safety of CP in the human body.